Corona-Krise: Staatsbeteiligungen bleiben eine problematische Intervention in den Markt - Klaus-Heiner Röhl; Christian Rusche (Wirtschaftsdienst, 2020)
Die Corona-Pandemie erfordert staatliche Eingriffe, um negative ökonomische Auswirkungen auf Konsumenten und Unternehmen abzumildern. Es bestehen jedoch auch Gefahren bei Interventionen durch den Staat: So können ineffiziente Strukturen konserviert werden, Märkte verzerrt und langfristig negative Struktureffekte ausgelöst werden. Deswegen ist es wichtig, dass der Staat bei seinen Interventionen auf Marktkonformität achtet. Das bedeutet, dass keine Strukturen geschaffen werden dürfen, die sich nicht auch am Markt hätten bilden können oder am Wettbewerbsrecht gescheitert wären. Staatliche Eingriffe sollten überdies nicht dazu genutzt werden, um politischen Einfluss auszuüben. – – The Coronavirus pandemic has presented society with major challenges that have required state intervention.. While government measures are necessary in an external crisis such as the current pandemic, negative effects can also arise from excessive government intervention, particularly for the economy. An analysis of the OECD countries shows that the state already played a major role in the economies of many countries before the coronavirus crisis, especially in Germany. However, state participation in companies does not necessarily have to lead to negative effects if it is structured appropriately. This article discusses how government measures, especially the extension of public ownership, should be designed in order to maintain competition and use the free market as an allocation instrument where possible. This means that no market structures should be created which could not have been created or which fail to comply with competition law. Moreover, state intervention should not be used to exert political influence on business decisions.
Keywords: E61; H12; O25; 330